The Asset Replacement Problem: State of the Art - Ansaripoor, Amir Hossein; Oliveira, F.; Liret, A. (Springer Heidelberg New York Dordrecht London, 2013)
In this book chapter we summarize how the asset replacement problem has evolved over time. We provide a broad view of different modeling approaches, including the economic life, the repair cost limit, comprehensive cost minimization models, and we analyze in detail the parallel replacement models. We suggest a new model for parallel replacement that addresses some of the issues not yet solved in this area. Finally, we discuss the limitations of the current models from a theoretical and applied perspective and identify some of the challenges still faced by academics and practitioners working on this topic